The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fendo.2022.888599
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of the Relationships Between Multiple Lipid Indices and Diabetic Kidney Disease in Patients With Type 2 Diabetes: A Cross-Sectional Study

Abstract: BackgroundDyslipidemia is a well-recognized risk factor for diabetic kidney disease (DKD) in patients with type 2 diabetes (T2D). Growing evidences have shown that compared with the traditional lipid parameters, some lipid ratios may provide additional information of lipid metabolism. Thus, the present study aimed to investigate which lipid index was most related to DKD.MethodsThis study was a cross-sectional study that enrolled patients with T2D from January 2021 to October 2021. Each participant was screened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Some studies have shown that AIP could represent the quantity of sdLDL particles (subfraction of LDL-C) [ 34 ]. sdLDL, characterized by difficulty in being cleared from the circulation, susceptibility to oxidation, and ease of uptake by macrophages to form foam cells, contributes to an elevated risk of microvascular complications [ 35 ]. Nonetheless, the clinical applicability of sdLDL is restricted because of its intricate and expensive measurement process [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that AIP could represent the quantity of sdLDL particles (subfraction of LDL-C) [ 34 ]. sdLDL, characterized by difficulty in being cleared from the circulation, susceptibility to oxidation, and ease of uptake by macrophages to form foam cells, contributes to an elevated risk of microvascular complications [ 35 ]. Nonetheless, the clinical applicability of sdLDL is restricted because of its intricate and expensive measurement process [ 13 ].…”
Section: Discussionmentioning
confidence: 99%